DPRD Secretariat Services in Supporting the Implementation of DPRD Duties and Functions in the Pangandaran District - Arie Budiawan; Kiki Endah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
This research examines the role and effectiveness of DPRD Secretariat services in supporting the implementation of DPRD duties and functions in the